Analysis of the flow in horizontal injector wells with profile equalization completion (Research, Society and Development, 2019)
Pressure losses due to friction can significantly influence the flux profile in horizontal injector wells, depending on their magnitude. Non-uniform flux profiles are responsible for the loss of injectivity and for the decrease in sweep efficiency, which are undesirable effects for oil recovery. In this context, the divergent perforation, or profile equalization completion, is a technique able to uniformize the flux profile by the differentiated distribution of the holes on the completion liner. This study used simulations of the flow in a pipe with differentiated perforation to analyze the flow in horizontal injector wells completed with the divergent perforation technique and the effect of both inertial and viscous forces on the pressure loss profile and, consequently, on the flux profile. The simulations realized at the Ansys 15.0 family software demonstrated that the flux profile follows the pressure loss trend on the horizontal section of the well. It was observed that the dominance of inertial forces resulted in more uniform flow profiles and so in better injectivity, while the dominance of the viscous forces resulted in the low influence of the hydraulic effects.